Emergencies and outcome in invasive out‐of‐hospital ventilation: An observational study over a 1‐year period. (16th August 2017) - Stieglitz, Sven; Matthes, Sandhya; Kietzmann, Ilona; Priegnitz, Christina; Hagmeyer, Lars; Randerath, Winfried
Abstract: Objectives: The number of ventilated patients is further increasing which leads to an increasing number of patients with weaning failure. In Germany, the treatment of patients with invasive out‐of‐hospital becomes more and more common. The aim of the study was to observe the outcome, the frequency and character of emergencies of patients with invasive out‐of‐hospital ventilation. Methods: We conducted a prospective study over 1 year. Fifty‐nine invasively ventilated patients living either at home or at nursing homes specialized in ventilator medicine were included. Results: Forty‐one (71%) of the patients were living in a nursing home. Chronic obstructive pulmonary disease (COPD) was the most common underlying disease (52.5%). Duration of daily ventilation did not change over the 1‐year period. 52.8% of the months went without a documented emergency. The most common emergencies were oxygen desaturation (29.6%), increase of secretion (12.2%) and dyspnea (8.7%). We found no difference in the frequency of emergencies between patients cared for in their own home compared with residential care. Ten patients died during the observation period. Fewer emergencies ( P = .02, CI 0.03‐0.85) was the only parameter associated with a reduced mortality. Frequency of emergencies as well as survival showed no difference regarding the way patients were cared for. Conclusions: In patients with invasive home mechanical ventilation survival for more than 1 year seems to be common. Only the rate of emergencies affected survival.